Collective Anomaly Perception During Multi-Robot Patrol: Constrained Interactions Can Promote Accurate Consensus - Madin, Zachary (Cranfield University, 2024)
Poster contribution to the Defence and Security Doctoral Symposium 2023
Keywords: Multi-robot patrol; collective learning; algebraic connectivity; collective consensus; DSDS23; DSDS23 Poster